Efeito de diferentes inseticidas sobre três linhagens de Trichogramma pretiosum Riley, 1879 (Hym.:Trichogrammatidae) em condições de laboratório - Prezotti, Lusinério (1993)
This work was carried out with the objective of determining the effects of some insecticides on the parasitism and development of three strains of Tríchogramma pretiosum Riley, 1879 (Hym.